Late Chant Compositions in the Kraków Gradual from the Fifteenth Century (Kraków, AiBKKK, Ms 45) .......... 237 (Graduał wawelski (Kraków, AiBKKK, Ms 45): Studium przypadku, 2025)
The Gradual from the Kraków Cathedral from the fifteenth century (Kraków, Biblioteka kapitulna, 45) is a valuable witness of a flourishing chant composition and performance in the late Middle Ages. Particularly melodious Alleluia chants were performed during Marian votive masses, often provided with strophic tropes. Most of the new Alleluia and sequences circulated from the fourteenth century onwards in Central Europe. A few of them document reverberation of the repertory that flourished in the adjacent Prague diocese, such as chants for St. Wenceslas or compositions by Prague archbishop Iohannes of Jenštejn. A new repertory is included in the main part of the Gradual and further inscriptions can be found mainly in the opening section with additions from the fifteenth and the sixteenth centuries. Here, several chants for Polish and Silesian saints and patrons – St. Stanislaus, St. Adalbert or St. Hedwig – were recorded, some of them probably written by local authors. Inscriptions of several pieces in the opening section of the manuscript suggest that performance of the monophonic melodies in a simple rhythm, the so-called “cantus fractus”, was also established in Kraków by the fifteenth century at the latest.